Generic Science Skills Profile of High School Students in Working on Chemistry Questions Based on Gender - Mustapa, Kasmudin; Nuryanti, Siti; Al Gifary, Muhammad (Universitas Pendidikan Ganesha, 2023)
The exploration of generic science skills in solving chemistry problems can be influenced by various factors, one of which is gender bias in the learning process. This research aims to measure students' generic skills in solving chemistry problems based on gender. This study is quantitative descriptive research with a pre-experimental method using a One-Shot Case Study design. The sample consists of 20 eleventh-grade students, with 10 male students and 10 female students, selected based on gender and the taught material. Data collection techniques include measurement techniques, observation techniques, and interview techniques. The data analysis technique used is quantitative descriptive analysis. The results of the research show difference in the scores of generic science skills between female and male students. Female students have higher scores in direct observation indicators (80 vs. 79) and logical inference (83 vs. 79). However, there is no significant difference in the cause-and-effect law indicator (74 vs. 74). Meanwhile, male students have a slight advantage in the abstraction indicator (67 vs. 66) and concept building (76 vs. 74). Of the five indicators examined in the form of tests, the abstraction indicator obtains the lowest score, while the highest score is in the logical inference indicator. From these results, there is no significant difference in the generic science skills of male and female students.